Stabilization of Sandy Slopes with Vetiver Grass Using Experimental Method and Mathematical Model - Contreras, Myrella Surichaqui (2024)
This paper proposes the evaluation of the feasibility of a bioengineering geotechnical solution for the control of natural slope landslides caused by soil susceptibility, because of natural events or human action. The engineering solution with environmental considerations involves using the vetiver plant (Chrysopogon zizanioides) to stabilize the natural slope. The methodology applied was the identification of soil characteristics through soil mechanics laboratory tests, knowledge of vetiver grass and slope stability analysis considering the experimental method (EM) and mathematical model (MM). The shear strength parameters obtained in the experimental method consider the cohesion and friction angle resulting from the direct shear test, while the second method only considers the additional cohesion resulting from the mechanical effect provided by the vetiver roots. The results of the research report that, in the experimental method, the safety factor of the global stability presents a smaller increase as the root of the plant grows compared to the mathematical method. Finally, the values of the safety factors obtained from the slope stability analysis modeled in the SLIDE geotechnical software are higher than the minimum values established in the Peruvian EC regulations. 020 Stabilization of soils and slopes under static and pseudo-static conditions.